Syukur dalam Perspektif al-Qur’an - Enghariano, Desri Ari (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
Gratefulness is one of commendable qualities. In the al-Qur’an uslub, this word of gratitude is expressed in term of gratitude. Islamic theaching consider this issue of gratitude important, so that in many verses of the holy Qur’an it can be found that the word gratitude is often couple with the word remembrance. Other terms that have some common meaning with it are al-hamdu and al-tsana’. The urgency of gratitude for a muslim is as a form of positive sel-actualization so that it can be a servant who is always obedient and grateful. Gratitude is very many benefits if done according to God instructions. Gratitude can be done by heart, verbally, and deeds. If a servant is grateful for the favor God has given him. But if a servant disobeys and does not thank God fro the grace he has enjoyed, then Allah will bring punishment upon him.